Involuntary Medication, Seclusion, and Restraint in German Psychiatric Hospitals after the Adoption of Legislation in 2013 - Flammer, Erich; Steinert, Tilman (Frontiers in Psychiatry, 2015)
Background: Involuntary medication in psychiatric treatment of inpatients is highly controversial. While laws regulating involuntary medication have been changed in Germany, no data has been available to date on how often involuntary medication is actually applied. Recently, our hospital group introduced specific routine documentation of legal status and application of involuntary medication in the patients’ electronic records, which allows the assessment of the frequency of involuntary medication. Method: For the year 2014, we extracted aggregated data from the electronic database on age, sex, psychiatric diagnosis, legal status during admission, kind of coercive measure (mechanical restraint, seclusion, and involuntary medication) applied, and the number and duration of seclusion and restraint episodes for seven study sites. Results: A total of 1,514 (9.6%) of 15,832 admissions were involuntary. At least one coercive measure was applied in 976 (6.2%) admissions. Seclusion was applied in 579 (3.7%) admissions, mechanical restraint was applied in 529 (3.3%) admissions, and involuntary medication was applied in 78 (0.5%) admissions. Two-thirds of involuntary medications were applied in cases of emergency; the remainder was applied after a formal decision by a judge. In 55 (70.5%) of the admissions with involuntary medication, at least one other coercive measure (seclusion, restraint, or both) was applied as well. Conclusion: Involuntary medication is rarely applied and less frequent than seclusion or mechanical restraint, possibly as a consequence of recent legal restrictions.